Investigating the Impact of Retail Outlet Attributes on Retail Patronage - Frempong, Joseph; Martey, Edward Markwe (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
The purpose of this study is to investigate the impact of retail outlets attributes on retail patronage in Ghana; the main objective is to study outlet attributes that are requisite to attract patronage. Two hundred and nine (309) questionnaires were returned, out of five hundred (500) questionnaires distributed through convenience sampling method to the population. With the aid of Statistical Package for Social Sciences (SPSS) the following statistics were employed: descriptive statistics, cranach’s alpha, kurtosis and skewness and Chi-square analysis was used to measure the impact of attributes (price, service quality, customer satisfaction, and brand image) on dependent variable (customer loyalty).The findings revealed that all four construct of customer retention; namely price, service quality, customer satisfaction, and brand image had a significant and positive relationship with customer loyalty. The research suggests that Customer Relationship Managers (CRMs) finds out what customers expect and serve them better and solve all customers’ complaints on time.